2017
DOI: 10.1021/acsbiomaterials.7b00432
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatibility of Ti3AlC2, Ti3SiC2, and Ti2AlN: In Vitro Tests and First-Principles Calculations

Abstract: Herein, the cytocompatibility of selected MAX phases, Ti3AlC2, Ti3SiC2, and Ti2AlN, were systematically evaluated using in vitro tests for the first time. These phases were anoxic to preosteoblasts and fibroblasts. Compared with the strong viable fibroblasts, the different cellular responses of these materials were clearly distinguishable for the preosteoblasts. Under an osteoblastic environment, Ti2AlN exhibited better cell proliferation and differentiation performance than Ti3AlC2 and Ti3SiC2. Moreover, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 68 publications
4
47
0
1
Order By: Relevance
“…[45] The presence of oxygen on the surface of the MAX phase is also detected (TiÀ O and AlÀ O peaks), showing that the MAX phase contains an oxide layer on the surface, in agreement with previous observations. [24,45] During the calcination of the Co 3 O 4 /Ti 2 AlC catalyst, the surface of the MAX phase changes ( Figure 6). The absence of characteristic TiÀ C and AlÀ Ti peaks indicates that the surface is partially oxidized during the preparation of the catalyst.…”
Section: Catalyst Testingsupporting
confidence: 91%
“…[45] The presence of oxygen on the surface of the MAX phase is also detected (TiÀ O and AlÀ O peaks), showing that the MAX phase contains an oxide layer on the surface, in agreement with previous observations. [24,45] During the calcination of the Co 3 O 4 /Ti 2 AlC catalyst, the surface of the MAX phase changes ( Figure 6). The absence of characteristic TiÀ C and AlÀ Ti peaks indicates that the surface is partially oxidized during the preparation of the catalyst.…”
Section: Catalyst Testingsupporting
confidence: 91%
“…This property motivated our inspiration that the diffused Al atoms from the Ti 2 AlN might form a good bond with the Al atoms inside the ZnAl alloy owing to the inherent chemical affinity between the Al atoms, and the strong interfacial bonding would be obtained. In addition, it was reported that Ti 2 AlN exhibited better cell proliferation and differentiation ability than Ti 6 Al 4 V alloy and pure Ti [32], which endowed it potential in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, the first step is to understand the biological responses of host tissue cells to the MXene biointerfaces. Chen et al investigated the biocompatibility of Ti 3 AlC 2 , Ti 3 SiC 2 , and Ti 2 AlN with preosteoblasts and fibroblasts through cell adhesion, proliferation, and differentiation and compared the results with pure Ti and Ti‐6Al‐4 V alloy as traditional Ti‐based materials used for implantation. Compared to noncoated Ti‐based specimens, the spreading of preosteoblast on MXenes, particularly Ti 2 AlN, was clearly promoted at initial stages of proliferation, reaching to 2901 µm 2 /cell.…”
Section: Biomedical Applications Of Mxenesmentioning
confidence: 99%
“…b) Contact angle experiment performed with deionized water to determine the hydrophilicity of surfaces. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Biomedical Applications Of Mxenesmentioning
confidence: 99%
See 1 more Smart Citation